Pengembangan Metode DGT (Diffusive Gradient In Thin Film) dengan Binding Gel Fe-Al-Oksida dan Pengikat Silang N,N’-Methylenebisacrylamide untuk Penyerapan Fosfat dalam Air - Asep Saefumullah; Ratsania Rahmaniati H (Jurnal Kimia Valensi, 2015)
High concentration of phosphates in the water can lead to eutrophication which leads to uncontrolled growth of algae (algae blooming). It underlies the need for determining the concentration of phosphate in the aquatic environment. However, the concentration of phosphate may change during storage of samples so that an accurate analysis difficult to achieve unless carried out in-situ. DGT (Diffusive Gradient in Thin Films) is an in-situ measurement method developed for measuring phosphate and metal. In this study the use of Fe-Al-Oxide as a binding gel that is expected to bind phosphate with a capacity greater than ferrihydrite. N, N'-methylenebisacrylamide is used as a substitute for commercial DGT Crosslinker as crosslinking for a cheaper price and selective for small molecule. Ferrihydrite-DGT and Fe-Al-Oxide-DGT are tested with a variety of concentrations, pH, and contact time. In both methods DGT found that the pH for phosphate measurements performed at pH 3. Capacity of Fe-Al-Oxide binding gel known to be higher than the ferrihydrite binding gel with result Cferrihydrite-DGT:Cstart is 76% and CFe-Al-Oxide-DGT:Cstart is 82%.DOI :http://dx.doi.org/10.15408/jkv.v0i0.3597